SENAM TERA UNTUK MENURUNKAN TEKANAN DARAH LANSIA DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI - Resmi Pangaribuan; Khairunnisa Batubara (Jukeshum: Jurnal Pengabdian Masyarakat, 2022)
Introduction: Elderly people experience health problems due to decreased organ function due to the aging process. Approximately 64% of elderly aged 60-74 years will experience an increase in blood pressure. Elderly people generally have a low level of physical fitness, especially in the components of cardio, respiratory, and muscle strength endurance. This can be done by doing good and correct physical exercise. Elderly gymnastics is very important for the elderly to maintain their body health like tera gymnastics. Tera gymnastics is an exercise that trains physically, mentally and can also improve and improve the condition and function of the heart and blood circulation, as well as control hypertension. Methods: the activities used in this community service program are in the form of counseling and demonstration of calibration exercises to reduce blood pressure (hypertension) at the Binjai Elderly Social Service UPT. Results: The elderly who participated in this counseling and demonstration understood how to lower blood pressure without medication by doing tera exercises and the elderly were able to do the exercises that he taught. The results obtained after carrying out these activities on the knowledge of the elderly showed that 65% of the elderly were willing to apply hypertension exercise at the Wisma (the house provided by the UPT).